1990
DOI: 10.1128/mcb.10.11.5634
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-specific polyadenylation and translational control: diversity of cytoplasmic polyadenylation elements, influence of poly(A) tail size, and formation of stable polyadenylation complexes.

Abstract: Early embryonic development in Xenopus laevis is programmed in part by maternally derived mRNAs, many of which are translated at the completion of meiosis (oocyte maturation). Polysomal recruitment of at least one of these mRNAs, G10, is regulated by cytoplasmic poly(A) elongation which, in turn, is dependent upon the cytoplasmic polyadenylation element (CPE) UUUUUUAUAAAG and the hexanucleotide AAUAAA (L. L. McGrew, E. Dworkin-Rastl, M. B. Dworkin, and J. D. Richter, Genes Dev. 3:803-815, 1989). We have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(159 citation statements)
references
References 26 publications
7
151
1
Order By: Relevance
“…Polyadenylation of reporter constructs was assessed by RT-PCR using a GST forward primer at the indicated times. B4 described in this study, an apparently contradictory CPEdependent regulation of histone-like B4 translation has been reported previously (14,43). These former studies, however, utilized a very truncated form of the 3Ј-UTR that lacked the 5Ј PRE identified in our study.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Polyadenylation of reporter constructs was assessed by RT-PCR using a GST forward primer at the indicated times. B4 described in this study, an apparently contradictory CPEdependent regulation of histone-like B4 translation has been reported previously (14,43). These former studies, however, utilized a very truncated form of the 3Ј-UTR that lacked the 5Ј PRE identified in our study.…”
Section: Discussioncontrasting
confidence: 40%
“…Both aspects of CPE function require the CPE-binding protein (CPEB) (9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…The role of poly(A) as a determinant of maternal mRNA translation during the meiotic maturation or subsequent fertilization of Xenopus oocytes is well established (Richter, 2000)+ This regulatory system discriminates between classes of mRNAs that are either polyadenylated or deadenylated during maturation+ One class of mRNAs, exemplified by G10, c-mos, and B4, contains the 39 UTR localized cis-sequences required for polyadenylation and subsequent translational activation (Dworkin & Dworkin, 1985;Fox et al+, 1989;McGrew et al+, 1989;Wormington, 1994)+ The cis sequences required for polyadenylation are the U-rich cytoplasmic polyadenylation element (CPE) and the ubiquitous nuclear polyadenylation element (AAUAAA) (McGrew & Richter, 1990;Paris & Richter, 1990)+ The deletion or mutational inactivation of either of these elements prevents both polyadenylation and translation (Fox et al+, 1989;McGrew et al+, 1989)+ In contrast, poly(A) removal is a default reaction deadenylating messages that lack a CPE such as those encoding ribosomal proteins and actin (Fox & Wickens, 1990;Varnum & Wormington, 1990)+ Deadenylated messages are dissociated from polysomes, thus preventing further translation+ Although the poly(A) tail is not necessarily sufficient for translatability (McGrew et al+, 1989), in no case has deadenylation been uncoupled from translational inactivation+ For example, the overexpression of poly(A)-binding protein (PABP) in Xenopus oocytes inhibits both maturation-specific deadenylation and translational silencing (Wormington et al+, 1996)+ The activity responsible for deadenylation in mature oocytes is initially nuclear associated, as poly(A) removal is a late maturation event that cannot be detected prior to nuclear envelope breakdown and is prevented if oocytes are enucleated prior to maturation (Varnum et al+, 1992)+ Importantly, Xenopus is the only system for which an in vivo function for deadenylation has been described (Fox & Wickens, 1990;Varnum & Wormington, 1990)+ The role of poly(A) in translation has been under intense scrutiny over the past few years (Sachs et al+, 1997;Sachs & Varani, 2000)+ The closed loop model of mRNA translation originally proposed by Munroe and Jacobson (1990) has been validated by subsequent biochemical and genetic evidence of interactions between the PABP and the cap-binding complex in yeast and mammalian systems (Tarun & Sachs, 1996;…”
Section: Introductionmentioning
confidence: 99%
“…In Xenopus and mouse (the only organisms examined to date in detail), cytoplasmic polyadenylation requires the presence of the nuclear polyadenylation signal AAUAAA proximal to a CPE (Richter, 1996)+ The function of the hexanucleotide is typically abolished by a U to G mutation (Fox et al+, 1989;Paris & Richter, 1990)+ In Drosophila, the exact signals for cytoplasmic polyadenylation remain to be delineated (see Discussion)+ The role of the hexanucleotide in clam RNA polyadenylation was examined by mutagenizing the RR 39 UTR AAUAAA 11 nt upstream from the A-tail to AAGAAA, and examining the ability of the resulting RNA to support polyadenylation+ In contrast to Xenopus, clam lysates modify this RNA to ;70% of wildtype levels (Fig+ 2B;Standart & Dale, 1993)+ FIGURE 2. Multiple CPEs in the RR 39 UTR+ A: Oocyte (top panel) and egg lysate polyadenylation assays (bottom panel) with full-length RR 39 UTR (1-454), or 1-454 RNA in which CPE a, b, a and b, e, and f were deleted (⌬a, ⌬b, ⌬ab, ⌬e, and ⌬f; see Fig+ 1A)+ Capped 32 P-labeled RNAs were analyzed by denaturing polyacrylamide gel electrophoresis before (Ϫ) and after (ϩ) addition of lysate and subsequent incubation for 2 h at 18 8C, followed by phenol extraction+ Extension of the RNAs by 150 residues was estimated from labeled DNA markers (not shown)+ B: Polyadenylation in egg lysate of wild type 1-454 RNA (AAUAAA) and 1-454 RNA with mutated NPE (AAGAAA)+ Ϫ, ϩ: as in A+ Note that the differing sizes of the RNA substrates are because of the different cloning cassettes in the wild-type and mutated constructs+…”
Section: P82 Has Multiple Binding Sites In Rr 39 Utr With Varying Afmentioning
confidence: 99%